Trade, market integration and spatial price transmission on EU pork markets following Eastern enlargement - Carsten Holst; Stephan von Cramon-Taubadel (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2013)
The accession of ten countries to the EU in May 2004, and of Bulgaria and Romania in January 2007, eliminated barriers to trade between old and new, and among new member states. We analyse the effects of this accession on the integration of pork markets in the EU. Our results show that the speed of price transmission is positively related to the volume of pork trade between two countries. Our results also reveal that intra-regional price transmission between old or between new member states is more rapid than inter-regional price transmission between old and new member states, and that producer prices in the new member states adjust more rapidly to price changes in the old member states than vice versa. Price transmission is also more rapid between Euro-zone members and member states that share a common border. Finally, our results show that the strengths of these effects have changed in predictable ways in the years since accession took place, as a single, increasingly integrated European pork market has evolved.
Keywords: 330; spatial price transmission; market integration; cointegration; European pork market